(untitled) (Global Journal of Science Frontier Research, 2015)
Bharweli mine is situated at 21 0 50′N latitude and 81 o 14′E longitude. It lies within the Manganese belt of Madhya Pradesh and adjoining parts of Maharashtra andforms an East-West trending arcuate belt of 150 Kms long. It is enclosed within the metasedimentary sequence of Sausar Group of rocks belonging to Precambrian age. Regionally, it is situated in Mansar Formation and rocks comprise of quartzite, sericite schist, phyllite and conglomerate. It also has some carbonate associations, containing stratiform manganese ore comprising Braunite, Bixbyte, Hollandite, Hausmannite, Pyrolusite and Psilomelane which form the largest manganese reserves in India.